The Routledge companion to arts management - Byrnes, William J; Brkić, Aleksandar (Routledge companions in business, management and accounting, 2020)
The Routledge Companion to Arts Management contains perspectives from international scholars, educators, consultants, and practitioners sharing opinions, exploring important questions, and raising concerns about the field. The book will stimulate conversations, foster curiosity, and open pathways to different cultural, philosophical, ideological, political, national, and generational insights. Four broad thematic areas are used to organize current topics in the field of arts and culture management. Part I introduces a mixture of perspectives about the history and evolution of the practice and study of arts management, the role of arts managers, and how arts management is being impacted by the digital age. Part II focuses on the dynamics of entrepreneurship, change processes, and leadership practices. Part III includes globally focused topics on cultural policy, cultural rights, and community building. Part IV examines a sampling of topics related to functional activities that are common to arts and culture organizations around the world such as marketing, planning, increasing diversity, hiring, fundraising, and sustainability. This book builds a comprehensive understanding of what arts management can mean in an international context creating an essential resource for students, scholars and reflective practitioners involved at the intersection of business and the arts.